The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2005
DOI: 10.1590/s1516-35982005000200040
|View full text |Cite
|
Sign up to set email alerts
|

Fontes de óleo vegetal na dieta de cordeiros em confinamento

Abstract: RESUMO -Objetivou-se avaliar a ingestão de matéria seca, o ganho de peso diário, a conversão alimentar, o peso vivo ao abate e o período de confinamento em cordeiros Santa Inês puros e ½Dorset ½Santa Inês, alimentados com dietas isoenergéticas (76,59% de NDT) e isoprotéicas (17,48% de PB) contendo diferentes fontes de óleo vegetal (óleos de soja, canola e linhaça) e uma dieta controle (sem inclusão de óleo vegetal). A relação volumoso:concentrado foi de 30:70 e utilizou-se feno de aveia como volumoso. Realizou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
1
12

Year Published

2010
2010
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 6 publications
1
9
1
12
Order By: Relevance
“…The conversion data reported in the present study were lower than those reported by Yamamoto et al (2005): 3.50; 3.57; 3.89 and 3.95 for Santa Inês × Dorper lambs, in confinement fed control diet and diet with (3%) soybean oil, rapeseed oil or flaxseed oil, respectively. The same occurred for daily weight gain when these authors reported an average of 0.272 (kg/day), higher than the means observed in the present experiment.…”
Section: Resultscontrasting
confidence: 90%
See 2 more Smart Citations
“…The conversion data reported in the present study were lower than those reported by Yamamoto et al (2005): 3.50; 3.57; 3.89 and 3.95 for Santa Inês × Dorper lambs, in confinement fed control diet and diet with (3%) soybean oil, rapeseed oil or flaxseed oil, respectively. The same occurred for daily weight gain when these authors reported an average of 0.272 (kg/day), higher than the means observed in the present experiment.…”
Section: Resultscontrasting
confidence: 90%
“…Yamamoto et al (2005) studied fat sources in feeding Santa Ines lamb reared in confinement and reported better performance for animals fed diet without soybean oil for weight gain compared with the diet with 3% of this ingredient. Several authors have reported reduction in rumen fermentation when fat was added to the diet (Santos et al, 2001b;Silva et al, 2007a, b;Oliveira et al, 2009;Silva et al, 2010).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Diets did not influence (P>0.05) leg compactness index, and average values were superior to the 0.30 leg compactness index found by Yamamoto et al (2005). Musselman et al (2008), working with 24 lambs, 24 ewes and 24 crossbred (Southdown × Suffolk) wethers, fed diets containing 0, 15, 30 and 45% crude glycerin of the total diet, reported similar commercial carcass yield results to those of this study, with 0 and 15% glycerin and a yield reduction for higher levels of glycerin.…”
Section: Resultsmentioning
confidence: 57%
“…According to Yamamoto et al (2005), Santa Inês breed has some undesirable characteristics concerning the meat production: slower weight gain and lower quality carcass compared to those of fitted breeds.…”
Section: Introductionmentioning
confidence: 99%